(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study examined the relationship between students’ false allegations and job satisfaction among university lecturers in two public universities in Delta State. Guided by one research question and one null hypothesis, the study adopted a correlational survey design. A total of 240 lecturers were sampled from the University of Delta, Agbor and Southern Delta University, Ozoro using stratified random sampling. Data were collected via structured questionnaires adapted from standardised instruments the WIS for students’ false allegations and the MSQ for job satisfaction with Cronbach’s alpha coefficients of 0.87 and 0.90, respectively. Descriptive statistics and Pearson’s product moment correlation were used for analysis. Findings revealed a very weak and non-significant negative relationship between students’ false allegations and lecturers’ job satisfaction (r = -0.044, p = 0.499), indicating that such allegations do not significantly influence overall job satisfaction. Based on the findings, the study recommends that universities implement clear complaint-handling procedures, provide stress management and counselling support, and enhance working conditions to promote lecturers’ professional wellbeing.